Clinical Practice Guidelines of Traditional Chinese Medicine Rehabilitation for Incomplete Paraplegia - Working Group of Clinical Practice Guidelines of Traditional Chinese Medicine Rehabilitation for Incomplete Paraplegia (康复学报)
The main clinical manifestations of incomplete paraplegia are sensation below the injury level and incomplete loss of motor or sphincter function. Rehabilitation intervention of traditional Chinese medicine (TCM) is one of the characteristic treatments of incomplete paraplegia, which has a good clinical effect. However, the TCM rehabilitation management, rehabilitation evaluation and rehabilitation treatment of incomplete paraplegia are not completely unified and standardized, and the rehabilitation outcome varies. The main purpose of formulating the "TCM Rehabilitation Guide" for incomplete paraplegia is to standardize the TCM rehabilitation management, rehabilitation evaluation and rehabilitation treatment for incomplete paraplegia, and to improve the outcome of rehabilitation diagnosis and treatment. The guide standardizes the rehabilitation clinical practice of incomplete paraplegia from the aspects of scope, terminology and definition, clinical diagnostic criteria, rehabilitation management, rehabilitation evaluation, rehabilitation treatment, syndrome differentiation etc. Rehabilitation management includes: the implementation of total quality management system; the establishment and improvement of an effective communication system; the formulation of staff training and development policies; the establishment of total quality management implementation mechanism and plan; the establishment of quality management inspection feedback mechanism and so on. Rehabilitation assessment includes: spinal cord injury neurological function assessment, muscle tone assessment, muscle strength assessment, psychological function assessment, activities of daily living and ability assessment and so on. Rehabilitation treatment includes: timing of TCM rehabilitation intervention, early rehabilitation treatment, rehabilitation treatment in recovery period, application of assistive devices and so on. We sort out the treatment, evidence level, recommended opinions and recommended prescriptions of different syndrome types of incomplete paraplegia, such as blood stasis syndrome, Qi deficiency and blood stasis syndrome, spleen and stomach weakness syndrome, liver and kidney deficiency syndrome, Qi and blood deficiency syndrome and so on. The guide is applicable to the rehabilitation departments of all levels and types of rehabilitation institutions, all TCM hospitals or general hospitals in China, and has good applicability and effectiveness.